ASSESSING THE STATIC OF SOIL-STRUCTURE INTERACTION ON THE BEHAVIOR OF REINFORCED CONCRETE STRUCTURES: A MECHANO-FIABILISTIC APPROACH - KAMEL BEZIH; MOHAMED DJENANE; MOHAMED LAOUCHE (Journal of Engineering Studies and Research)
Assuring the lifespan and safety of reinforced concrete (RC) structures is essential, given the potential risks of malfunctions such as premature failure. To meet this challenge and construct durable, cost-effective structures, consideration of soil-structure interaction and inclusion of soil resistance elements in mechanical evaluations are critical. This study uses a numerical model based on the finite element method to examine the impact of inherent non-linearities in the soil on the performance of a three-span RC beam. The numerical study highlights the crucial role of soil geotechnical parameters. It clarifies the complex static non-linear effects that result from the interaction of the soil and the structure. The work also introduces a mechano-fiabilistic method, emphasizing how soil behavior in traditional RC structure designs is unexpected and non-linear. The sensitivity of structural safety to changes in soil parameters is revealed by integrating static modeling of the soil-structure interaction into the mechanical model of a continuous beam. This study emphasizes how important it is to incorporate soil-structure interaction into RC structure designs for precise, dependable, and economical results.